Pengembangan dan Evaluasi Game Edukasi ICOTYPE untuk Melatih Keterampilan Mengetik: Development and Evaluation of ICOTYPE Educational Game to Train Typing Skills - Hersanto, Agung; Sukirman, Sukirman (ITScience (Information Technology and Science), 2024)
Innovations in information and communication technology have brought about a transformation in the world of education, especially in typing skills that are essential for academic and professional efficiency and productivity. However, traditional typing instruction is often considered monotonous and uninteresting, which reduces students' learning motivation. This study proposes the development of an educational game called ICOTYPE to train typing skills quickly and accurately through interactive and interesting methods. This study aims to evaluate the effectiveness of ICOTYPE in improving typing speed and accuracy and motivating students in the learning process. The research method used is Research and Development (R&D) with the 4D model (Define, Design, Develop, and Disseminate). The study participants consisted of 30 junior high and high school students aged 14-18 years. Data were collected through questionnaires that assessed user experience, psychological aspects, and typing performance, data analysis applied using the Partial Least Squares Structural Equation Modeling method. The results showed that ICOTYPE was effective in improving students' typing skills and learning motivation. This game provides an interactive learning environment, reduces boredom, and increases student engagement. These findings support the use of educational games as an effective alternative method in teaching typing and provide educational game developers with insights into effective components in designing learning products. This study also indicates the potential for integrating game-based approaches into educational curricula to teach practical skills such as typing, which are essential in today's digital age.